Impunity for Sale: Are Deferred Prosecution Agreements a Way for Companies to Evade Liability? (TEST Trento Student Law Review, 2024)
Deferred Prosecution Agreements (DPAs) have emerged as a contentious legal instrument, as they allow corporations to negotiate their way out of criminal liability without facing the full weight of a trial. This paper aims to explore the inherent benefits of DPAs – such as the potential for corporate reform, cooperation with law enforcement, preservation of jobs, and economic stability – while highlighting the criticisms, including concerns about accountability, transparency, and the perception of impunity. This article argues that, when appropriately structured and administered, DPAs provide benefits that significantly outweigh their drawbacks, as they offer a practical and flexible solution for addressing corporate wrongdoing where traditional criminal prosecution may be impossible or excessively burdensome. Nevertheless, their current limitations call for legislative amendments aiming at achieving a fairer and more comprehensive legal framework. These changes should address issues such as ensuring transparency in DPA negotiations, establishing clear criteria for DPA eligibility, and enhancing judicial oversight.
Keywords: Deferred Prosecution Agreements; Negotiated Justice; Law Enforcement Cooperation; Impunity Concerns; Legislative Amendments